Towards the visualization of usage and decision knowledge in continuous software engineering - Johanßen, Jan Ole; Kleebaum, Anja; Paech, Barbara (2017 IEEE Working Conference on Software Visualization, 2017)
Continuous software engineering (CSE) includes activities to continuously evolve software artifacts. Along with these activities, developers employ knowledge such as usage and decision knowledge. Usage knowledge helps developers to understand how users apply software, while decision knowledge comprises all decisions taken during CSE and their rationale. However, due to the frequency, extent, and complexity of knowledge in CSE environments, accessing and processing knowledge is challenging for developers. We propose a dashboard for developers that visualizes knowledge from various sources. This enables developers to follow, reflect, interact, and react on knowledge in CSE environments. We introduce springboards that serve as knowledge selectors while the selected extract of knowledge is visualized in widgets. Widgets allow developers to gain insight into knowledge. We suggest three widget classes: spot, compare, and range. We discuss dashboard extensions such as interaction triggers to add, modify, or combine knowledge. We plan to implement the dashboard and evaluate it with teams during software development projects in an industrial setting.
Gesehen am 20.07.2018
Keywords: Konferenzschrift